The use of β-glucan extracted from baker’s yeast (Saccharomyces cerevisiae) to increase non-specific immune system and resistence of tilapia (Oreochromis niloticus) to Aeromonas hydrophila - Jamal, Ida N; Tumbol, Reiny A; Mangindaan, Remy E.P (AQUATIC SCIENCE & MANAGEMENT, 2013)
Motile Aeromonas Septicaemia disease (MAS) attacking tilapia has increased in recent years as a consequence of intensive aquaculture activities, which led to losses in aquaculture industry. The agent causing MAS disease is Aeromonas hydrophila. The disease can be controlled with the β-glucan. As immunostimulants, β-glucans can also increase resistance in farmed tilapia. Studies on the use of β-glucan extracted from baker's yeast Saccharomyces cerevisiae was intended to evaluate the non-specific immune system of tilapia that were challenged with Aeromonas hydrophila. The method used was an experimental method with a completely randomized design consisting of four treatments with three replicats. The dose of β-glucan used as treatments were 0 mg.kg-1 fish (Control), 5 mg.kg-1 fish (B), 10 mg.kg-1 fish (C) and 20 mg.kg-1 fish (D), each treatment as injected three times at intervals of 3 days, the injection volume of 0.5 ml/fish for nine days and resistance surveillance for seven days. The results showed that the difference in the amount of β-glucan and the frequency of the injected real influence on total leukocytes, phagocytic activity and resistance. Total leukocytes, phagocytic activity and resistance to treatment was best achieved by the administration of C a dose of  10 mg.kg-1 of the fish© Penyakit Motil Aeromonas Septicaemia (MAS) yang menyerang ikan nila mengalami peningkatan selama beberapa tahun terakhir sebagai konsekuensi dari kegiatan akuakultur intensif, yang menyebabkan kerugian dalam industri budidaya. Agen utama penyebab penyakit MAS adalah Aeromonas hydrophila. Untuk mengendalikan penyakit tersebut dapat dilakukan dengan pemberian β-glukan. Sebagai imunostimulan, β-glukan juga dapat  meningkatkan resistensi pada ikan nila yang dibudidayakan. Pengkajian mengenai pemanfaatan β-glukan yang diekstrak dari ragi roti Saccharomyces cerevisiae dimaksudkan untuk menguji sistem imun non spesifik ikan nila yang diuji tantang dengan bakteri Aeromonas hydrophila. Metode yang digunakan yaitu metode eksperimen dengan rancangan acak lengkap yang terdiri dari empat perlakuan dan tiga ulangan. Dosis β-glukan  yang digunakan sebagai perlakuan sebesar 0 mg.kg-1 ikan (Kontrol), 5 mg.kg-1 ikan (B), 10 mg.kg-1 ikan (C) dan 20 mg.kg-1 ikan (D), masing-masing perlakuan diinjeksi sebanyak 3 kali dengan interval waktu 3 hari selama 9 hari, volume injeksi 0,5 mL/ekor ikan dan pengamatan resistensi selama tujuh hari. Hasil penelitian menunjukkan perbedaan jumlah β-glukan dan frekuensi pemberian yang diinjeksikan memberikan pengaruh nyata terhadap total leukosit, aktivitas fagositosis dan resistensi. Total leukosit, aktivitas fagositosis dan resistensi terbaik dicapai pada perlakuan C dengan dosis 10 mg.kg-1 ikan©